Defining relative humidity in terms of water activity. Part 2: relations to osmotic pressures. (21st December 2018) - Feistel, Rainer
Abstract: Relative fugacity (RF), or relative activity, of water in humid air has recently been suggested as a real-gas generalisation for relative humidity, the latter being conventionally defined as a ratio of partial pressures of water vapour. The RF definition covers the entire temperature-pressure region below the critical point of water, where humid air remains a gas, in an unambiguous and continuous manner. However, while thermodynamically rigorous, the theoretical definition of RF does not provide experimental methods of measuring RF of given samples of humid air, nor of preparing reference materials of specified RF, such as for humidity-sensor calibration purposes. In this paper, the osmotic pressure of humid air with respect to pure water in different phases, mutually separated by a semi-permeable membrane, is proposed as an SI-traceable measurand for the calculation of RF over the full range of sub-saturated states. The method of osmotic pressures offers a theoretical option for the experimental determination of the RF of humid-air samples without use or knowledge required on their actual or saturation composition, without exploiting an empirical equation for the fugacity, or an equation of state of humid air.